Divine secrets of the Ya-Ya Sisterhood : a novel - Wells, Rebecca, 1952- (New York, NY : HarperPerennial, 1997)
At thirty-nine, SiddaLee Walker has escaped her Louisiana hometown to become a theatrical director, but as she gathers old letters, photos, journals, and souvenirs from the Ya-Ya Sisterhood to assist in writing a play about women's friendships, she yearns to revisit her childhood.
Accelerated Reader AR
Keywords: Mothers and daughters -- Fiction; Friendship -- Fiction; Families -- Fiction; Domestic fiction